PENGARUH PEMBELAJARAN KOOPERATIF DENGAN METODE SNOWBALL THROWING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 2 RAMBAH HILIR - Setiawati, Titik Endang; Deswita, Hera; -, Suwandi (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
This research aims to determine the effect of metode Snowball Throwing against the results of learning mathematic in students class VIII at State Junior High School Rambah Hilir. Data collection techniques using the post test. The writer used test âtâ in analyzing the data. Based on data analysis the writer thitung = 2,915 and ttabel = 2,00 at taraf 5%. It show that thitung > ttabel. Therefore the metode Snowball Throwing influence to the result of learning mathematic in students class VIII at State Junior High School Rambah Hilir